Histoire en jeux : Jeux de société produits en France dans le long XIXe siècle (Histoire en jeux · Corpus INVISU)
Issue des recherches menées dans le cadre du programme « Histoire en jeux » au sein du laboratoire InVisu (CNRS) et à l’Institut National d'Histoire de l'Art, cette base a pour vocation de valoriser des collections de jeux de société anciens issues de fonds particuliers et d’institutions publiques, et de rendre ces sources originales et variées accessibles à la communauté des chercheuses et chercheurs, ainsi qu’aux enseignantes et enseignants, amatrices et amateurs. Le programme « Histoire en jeux » examine les jeux commercialisés en France au cours du long XIXe siècle, de la Révolution française à la fin de la Première Guerre mondiale. Il propose d'analyser la manière dont divers aspects de l’histoire culturelle (et notamment la diffusion des savoirs historiques) sont abordés sous le format ludique à travers un corpus principalement constitué de jeux, tels quels les lotos, jeux de l’oie, jeux de cartes, puzzles (patiences), ou petits théâtres de papier. Il se penche en priorité sur les jeux produits à moyenne voire à grande échelle, en évitant d’accorder une importance disproportionnée aux jeux et jouets les plus luxueux, réservés aux élites. Dans cette optique, il s’intéresse plus spécifiquement aux jeux et jouets constitués d’illustrations sur papier et de cartonnage, dont le coût relativement bas permet une ample diffusion. La base de données se veut une ressource ouverte aux spécialistes de disciplines variées, en référençant des jeux qui mettent en œuvre de multiples croisements entre la culture visuelle, littéraire, scientifique ou politique de leur temps.
Keywords: _open access

Residential Schools Locations Project
This dataverse contains datasets associated with the Residential Schools Locations Project. This datasets in this project show the precise locations of the Residential Schools (Boarding Schools, Industrial Schools and Hostels) in Nova Scotia, Quebec, Ontario, Manitoba, Saskatchewan, Alberta, British Columbia, Yukon Territory, Northwest Territories and Nunavut. Data was created by Rosa Orlandini with significant contributions from the National Centre for Truth and Reconciliation, and minor contributions from Morgan Hite and Stephanie Pyne.
Keywords: _open access

Historical Atlas of Canada Online Learning Project
Data for maps from the Historical Atlas of Canada Online Learning Project (HACOLP), preserved here largely for preservation purposes. HACOLP was a series of interactive online maps based on maps in the published Historical Atlas of Canada series. Data deposited by Byron Modolfsky, cartographer for the Historical Atlas of Canada, summer 2019.
Keywords: _open access

The Canadian Peoples 1871-1921 census data
The Canadian Peoples (TCP) data infrastructure encompasses 40 million coded and georeferenced census records from 1852-1921 including personal, family and household characteristics for every individual in each enumeration. The Canadian Foundation for Innovation, provincial research funds in Quebec, Ontario and Alberta, nine Canadian universities and Ancestry.com have funded the project. The owner of these data, Ancestry.com, has agreed to license their use for academic research and educational purposes only, with no right to publish, transfer, share, sub-license or distribute any portion of the data. Access to data for research and educational purposes may occur upon approval of a completed application by the TCP approvals committee. Any research institution or research seeking access to any of the data within this collection will need to complete the application form and send it to the TCP project director Kris Inwood at: kinwood@uoguelph.ca The first census year for distribution is 1871; the data for other years will follow as soon as they can be made ready.
Keywords: _open access

La Commune de Paris - Audin, Michèle (La Commune de Paris)
Blog de Michèle Audin
Keywords: _open access

Ingenium (Musée des sciences de l’innovation du Canada)
Ingenium – Le Musée des sciences de l’innovation du Canada à Ottawa crée des expositions hors concours, des programmes accessibles et adaptés aux familles ainsi que des recherches collaboratives qui prennent vie grâce à notre collection nationale d’artefacts.
Keywords: _open access

Base de données Léonore (Légion d'honneur)
Accès aux dossiers nominatifs des personnes nommées ou promues dans l'Ordre de la Légion d'honneur depuis 1802 et décédées avant 1977. Les dossiers originaux sont conservés aux Archives nationales ou à la Grande Chancellerie de la Légion d'honneur.
Keywords: _open access

Corpus Académie française (ORTOLANG)
Le Corpus Académie française est un corpus lemmatisé et étiqueté des textes publiés sur le site de l'Académie française dans les rubriques « Discours », « Dire, ne pas dire » et « Questions de langue. 1635 à nos jours.
Keywords: _open access

Repairs. Réparations, compensations et indemnités au titre de l’esclavage (Europe-Amériques-Afrique) (XIXe-XXIe) (Esclavages CIRESC)
Cette carte s’inscrit dans le cadre du projet de recherche « Repairs. Réparations, compensations et indemnités au titre de l’esclavage (Europe-Amériques-Afrique) (XIXe-XXIe) » financé par l’ANR, Agence nationale de la recherche. Le projet Repairs est porté par trois institutions : le CIRESC, Centre international de recherche sur les esclavages et post-esclavages (CNRS) ; l’ISJPS, Institut des sciences juridique et philosophique de la Sorbonne (Université Paris 1 Panthéon Sorbonne, CNRS) ; l’URMIS, Unité de Recherche Migration et Sociétés (IRD, CNRS, Université de Paris, Université Côte d’Azur).
Keywords: _open access

Digitized Diaries - Hunter, David (The Diary Index, 2015)
This list of open access, digitized diaries is designed to assist students and scholars interested in studying diaries.
Keywords: _open access

The New Montreal gazette 1834 - Canadianaorg (Printed and Published by Robert Weir, Junior, 1834)
Keywords: _open access

France China Archives
France China Archives est une plateforme en libre accès qui inventorie les archives photographiques de la Chine conservées en France. Elle prend en compte les fonds privés et publics dont le contenu couvre la période allant des années 1840 à nos jours. Cette plateforme a été pensée pour fournir un espace numérique savant à l’étude de la variété des pratiques photographiques en Chine, tout en rendant les ressources en français accessibles à la communauté scientifique, aux étudiants et au grand public.
Keywords: _open access

Chinese Women's Studies Database glossary | Cheng Yu Tung East Asian Library
The Chinese Women’s Studies database is a unique resource for information about women’s social conditions, women’s movements and the rise of feminism in China. It is built upon a collection of card records donated to Cheng Yu Tung East Asian Library in the early 1980s by Dr. Bobby Siu, who was then a PhD student of Carleton University, Ottawa, Ontario. He collected the information and put it down on thousands of cards while he was conducting research on Chinese women. The records were all handwritten in either English or Chinese. Topics covered range from education and marriage to women's movement as well as revolutions and wars.
Keywords: _open access

Chinese collections at the Bodleian Libraries - Bodleian Libraries (2024)
Chinese books have been part of the Bodleian Libraries’ collections since the Library’s foundation in 1602. The first known acquisition of a Chinese book dates to 1604. Our founder – Sir Thomas Bodley – was instrumental in starting this collection, even though he did not speak or understand Chinese.  His handwriting appears in the 1604 book. The collection grew over the following four centuries and it continues to grow today. It is now one of the most significant Chinese rare book and manuscript collections outside China, containing the largest number of Chinese books that arrived in Europe in 17th century. As part of a ten-year project funded by Chung Hon Dak Foundation, we have digitised over 1,800 items, as well as worked with the local Chinese community to explore our collections in more detail.
Keywords: _open access

Collections numériques de l’Institut Français de Pondichéry - Inist (2024)
Keywords: _open access

Revue canadienne (Canadiana)
1864-1920
Keywords: _open access

The Canadian magazine (Canadiana)
1893-1921
Keywords: _open access

Historic UK Newspaper Datasets (2024)
This dataset contains text extracted at the article level from historic digitised newspapers from the Heritage Made Digital newspaper digitisation program at the British Library. The newspapers in the dataset were published between 1800 and 1896. This dataset contains ~2.5 billion tokens and 3,065,408 articles. The dataset contains text generated from Optical Character Recognition software on digitised newspaper pages. This dataset includes the plain text from the OCR alongside some minimal metadata associated with the newspaper from which the text is derived and OCR confidence score information generated from the OCR software.
Keywords: _open access

The Maryland Motherlode: Births, Marriages, Deaths, and Naturalizations (Reclaim The Records)
Keywords: _open access

Canada Census Search - Library and Archives Canada
Application Description
Keywords: _open access

The Valley of the Shadow: Two Communities in the American Civil War
Keywords: _open access

UW-Madison Libraries Collections
Keywords: _open access

American Baptist Historical Society (American Baptist Historical Society, 2023)
The American Baptist Historical Society (ABHS) holds the archives and serves as the historical interpreter of a major religious denomination — American Baptist Churches USA — made up of 4,900 churches and 1.2 million people. ABHS archival collections include records from many different Baptist organizations in North America and around the world. As the oldest Baptist historical society (founded in 1853) with the largest and most diverse collection of Baptist historical material, our holdings are of irreplaceable value to church, national, and global history. ABHS serves as keeper of the record of the modern missionary movement. Our shelves hold unparalleled resources documenting African-American church associations, women’s work, local church and association minutes, and the social gospel movement. We publish the oldest Baptist journal, Foundations, interpreting for modern readers the lives and issues of the past that shape who we are today.
Keywords: _open access

Daniel A. P. Murray Pamphlet Collection (Library of Congress)
"African American Perspectives" gives a panoramic and eclectic review of African American history and culture and is primarily comprised of two collections in the Rare Book and Special Collections Division: the African American Pamphlet Collection and the Daniel A.P. Murray Collection with a date range of 1822 through 1909. Most were written by African-American authors, though some were written by others on topics of particular importance in African-American history. Among the authors represented are Frederick Douglass, Ida B. Wells-Barnett, Benjamin W. Arnett, Alexander Crummel, Emanuel Love, Lydia Maria Child, Kelly Miller, Charles Sumner, Mary Church Terrell, and Booker T. Washington, among others.
Keywords: _open access

African American Women Writers of the 19th Century - Divisions, Schomburg Center Research (NYPL)
African American Women Writers of the 19th Century guide includes a digital collection of published works by 19th-century black women writers, biographies for each author, citations and much more
Keywords: _100+; _open access

The Black Press
Keywords: _open access

Artefacts Canada - Gouvernement du Canada, Ministère du Patrimoine canadien
Artefacts Canada propose un accès à de l'information sur des millions d'objets de musées, fournis par des musées et des organismes patrimoniaux de partout au Canada.
Keywords: _open access

Women Working, 1800-1930 (CURIOSity Digital Collections)
An exploration of women's impact on the economic life of the United States between 1800 and the Great Depression.
Keywords: _open access

Eugenics Archive
Keywords: _open access

Chronicling America - National Endowment for the Humanities (Library of Congress)
Search America's historic newspaper pages from 1770-1963 or use the U.S. Newspaper Directory to find information about American newspapers published between 1690-present.
Keywords: _open access